Case study: Treating infraspinatus and supraspinatus trigger points and supraspinatus tendinopathy utilizing piezoelectric shockwave - Owen, Heather (Frontiers in Veterinary Science, 2022)
Two individual case studies demonstrate piezoelectric shockwave treatment for resolution of a supraspinatus tendinopathy and supraspinatus and infraspinatus myofascial trigger points via musculoskeletal ultrasound. This is the first documentation of improvement of both tendon and muscle fiber pattern in canine patients treated with piezoelectric shockwave. These cases validate the use of piezoelectric shockwave during rehabilitation of common canine shoulder injuries.